2012
DOI: 10.1007/s10354-012-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of cardiac calcium handling

Abstract: Cardiac calcium (Ca(2+)) handling subsumes the mechanisms maintaining the myocardial Ca(2+) homeostasis that contribute essentially to cardiac performance. This review addresses the interaction of transplasmalemmal and transsarcoplasmic Ca(2+) flux, its potential modifications due to β-adrenergic stimulation and its implications on cardiac action potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, the major stimulus for controlling PLB activity is related to the β adrenergic system, since it PLB phosphorylation at serine 16 regulates SERCA2a activity, which may hampering or not recapturing Ca 2+ from sarcoplasmic reticulum. This injury is related to lusitropic damage to cardiac tissue [ 68 ]. The transcription signal or signals responsible for triggering the actions of the β-adrenergic system grafting occur because catecholamines or adrenergic agonists bind to their receptors, acting as first messenger in the β-adrenergic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the major stimulus for controlling PLB activity is related to the β adrenergic system, since it PLB phosphorylation at serine 16 regulates SERCA2a activity, which may hampering or not recapturing Ca 2+ from sarcoplasmic reticulum. This injury is related to lusitropic damage to cardiac tissue [ 68 ]. The transcription signal or signals responsible for triggering the actions of the β-adrenergic system grafting occur because catecholamines or adrenergic agonists bind to their receptors, acting as first messenger in the β-adrenergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This cascade of events leads to changes in the activity of proteins including L-type calcium channels [ 26 , 69 ], phospholamban [ 70 ], troponin I [ 71 ] and ryanodine receptors [ 72 ], altering cardiac function [ 22 ]. Thus, the adrenergic stimulation increases the inotropy (contractile force), chronotropy (heart rate), dromotropy (excitation conductance), bathmotropy (decrease in threshold of excitation) and lusitropy (relaxation) of cardiac tissue [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only a few studies that have reported impaired intracellular Ca 2+ handling leading to myocardial dysfunction in OR rodents. In cardiac myocytes, Ca 2+ plays an important role in cardiac performance and physiological processes 15 , 36 . According to Bögeholz et al 36 , there are three main ways to modulate the contractile function of myofilaments, namely (1) alteration of cytosolic Ca 2+ concentration, (2) mechanical change in pretension, and (3) catecholaminergic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of acto-myosin binding is therefore associated with increased intracellular calcium concentration. 29 Changes in the calcium transient directly affect contraction and relaxation dynamics and short- and long-term power output of the heart, making it a potent regulator of transient and long-term cardiac mechanotransduction. 30 …”
Section: The Sarcomerementioning
confidence: 99%